Factors And Tools Which Affect the Implementation and Continuous Improvement of The Performance Management System: Findings from A Questionnaire Survey in Slovak Companies - Lucie LENDELOVÁ; Petra FEJOVÁ; Viliam LENDEL (Communications of International Proceedings, 2021)
In today's highly competitive and dynamic business environment companies need performance management system for managing of their performance and fulfill their strategy. Based on this they are able to be more competitive and gain the competitive advantage. The implementation of performance management system and also performance measurement system is not easy process and it is necessary to change and transform the system over time and ensure the continuous improvement of the system. There exist internal and external factors which influence implementation and continuous improvement of these systems and also are identified some tools which ensure continuous improvement of systems. This paper deals with this issue and through the questionnaire survey on the sample of selected middle and large companies in Slovakia are analyzed factors which influence the implementation and continuous improvement of performance management systems and are identified tools used for improvement of these systems.
Keywords: Performance Management System; Factors; Tools; Improvement